Assessment of Oral Hygiene Status and Practices among a Sample of 12-Year-Old Chepang Children of Nepal - Adhikari, Santosh; Humagain, Manoj; Tamrakar, Lucky (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Introduction: Hygienic oral health practices are necessary from a young age to ensure positive long-term oral and general health. The oral hygiene status and practices among the underprivileged Chepang children of Nepal have not been adequately assessed. Objective: To assess the oral hygiene status and practices among the 12-year-old Chepang children of Nepal, and to identify the association of demographic variables and oral hygiene practices with the oral hygiene status of the children. Methods: This was a descriptive cross-sectional study where a pretested questionnaire was used to assess the oral hygiene practices and the simplified oral hygiene index (OHI-S) to examine the status of oral hygiene among 160 Chepang children of central Nepal. Statistical analysis was done with SPSS v.17. Statistical significance was determined using an independent t-test and an ANOVA test. Results: The study showed that 68 (42.5%) of the 12-year-old Chepang children had good oral hygiene, 68 (42.5%) had fair oral hygiene, and only 24 (15%) had poor oral hygiene. The mean OHI-S score for them was 1.62±1.09. Most of the children (138, 86.3%) regularly brushed their teeth and rinsed their mouth after meals (117, 73.1%), but tongue cleaning was performed by only 36 (22.5%) of them. Conclusions: The study showed that oral hygiene intervention programs are needed for the Chepang children who do not go to schools and who do not stay at hostels.